Study on the Behavior of Self-Cleaning Impregnated Photocatalyst (Tio2) with Cement Mortar - Chandrasekaran Palanisamy; Ganeshprabhu Parvathikumar; S. Gnanasekaran; Samson Jerold Samuel Chelladurai; S. Sivananthan; B. Adhavan; N. K. Geetha; Ramesh Arthanari; Solomon Tibebu (Advances in Materials Science and Engineering)
Cement-based materials are increasingly and widely employed in infrastructure development; however, they pollute our environment by generating carbon dioxide, which is detrimental to our civilization. In self-cleaning concrete, photocatalysts accelerate the decomposition of organic particles; thus, photocatalytic degradation of gaseous pollutants could reduce pollution. The incorporation of photocatalytic components enhanced the mechanical self-cleaning properties of cement mortar. In this study, 4–6 percent by weight of rutile TiO2 was added to mortar, and the results were compared to those of a control sample. On the proposed mortar cubes, both fresh mortar and hardening mortar experiments were conducted. Because the initial and final setting times of TiO2 differ from those of conventional cement mortar, the surplus TiO2water-cement ratio had to be modified. The adaptability of the sol-gel method enables the use of various process parameters to influence the properties of the produced TiO2 nanoparticles. The compressive strength was calculated for 7, 14, 21, and 28 days, and an ultrasonic velocity test was performed after 28 days. On mortar samples, acid and sulfate attack experiments were performed. The M-3 mortar mixture containing 5% rutile exhibited the highest level of strength compared to the other mixtures. The M-3 exhibits a strength that is 10.96% greater than that of the control mix. The impact of acid and sulfate attack on the strength of mix M-2 is relatively modest in comparison to other mixtures. Using RhB (rhodamine color) discoloration under UV light, such as sunlight, the photocatalytic mortar is concentrated; a typical test for self-cleaning cementitious materials reveals the presence of more photocatalytic material, which yields the best results.